Analisis Kinerja Jaringan Wi-Fi di RS Gading Pluit untuk Meningkatkan Produktivitas Pengguna Menggunakan metode QoS - Malau, Sadrak; Limbong, Albinur (TeIKa, 2024)
Wi-Fi network performance is critical in a healthcare environment in a hospital, where efficient communication and access to information are essential. This study analyzes the performance of a Wi-Fi network in Gading Pluit Hospital using the Quality of Service (QoS) method. The main focus of this study is the evaluation of QoS parameters such as delay, jitter, throughput, and packet loss to identify areas that need improvement in the network infrastructure. The test results show that throughput has a stable network and packet loss is at a very good level which supports network stability. Delay is mostly in the good to very good category, although there are fluctuations. However, jitter shows significant variability in some locations, indicating the need for further optimization, especially for time-sensitive applications such as voice or video communication.